2018
DOI: 10.1186/s12906-018-2300-z
|View full text |Cite
|
Sign up to set email alerts
|

Sotetsuflavone inhibits proliferation and induces apoptosis of A549 cells through ROS-mediated mitochondrial-dependent pathway

Abstract: BackgroundSotetsuflavone is isolated from Cycas revoluta Thunb., which has biological activity against tumors. However, the anti-proliferative effects of sotetsuflavone on A549 cells and its mechanism are not fully elucidated.MethodsThis study investigated the mechanisms of growth inhibition, cell cycle arrest and apoptosis in non-small cell lung cancer A549 cells induced by sotetsuflavone and evaluated whether sotetsuflavone can be safely utilized by humans as therapeutic agent.ResultsWe found that sotetsufla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Previously, we demonstrated that sotetsuflavone was able to inhibit the migration and invasion, and able to induce apoptosis and cycle arrest of A549 cells (Wang et al, 2018a;Wang et al, 2018b). Thus, we used Cell scratch assays, Transwell invasion assays, Tunel assays, and flow cytometry to test whether or not sotetsuflavone was able to inhibit the migration and invasion, as well as induce apoptosis and cell cycle arrest in H1650 cells.…”
Section: Sotetsuflavone Inhibits the Migration And Invasion And Indumentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we demonstrated that sotetsuflavone was able to inhibit the migration and invasion, and able to induce apoptosis and cycle arrest of A549 cells (Wang et al, 2018a;Wang et al, 2018b). Thus, we used Cell scratch assays, Transwell invasion assays, Tunel assays, and flow cytometry to test whether or not sotetsuflavone was able to inhibit the migration and invasion, as well as induce apoptosis and cell cycle arrest in H1650 cells.…”
Section: Sotetsuflavone Inhibits the Migration And Invasion And Indumentioning
confidence: 99%
“…In the early stages of analysis, we used the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) method to detect the function and effects of sotetsuflavone on the viability of A549 cells. Results indicated that sotetsuflavone had a strong inhibitory effect on the levels of activity of A549 cells (Wang et al, 2018a). To further verify whether or not sotetsuflavone is a potent inhibitor of A549 cell proliferation, we used 5-ethynyl-20-deoxyuridine (EDU) and colony formation experiments.…”
Section: Sotetsuflavone Inhibits Proliferation Of Nsclc Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…is an evergreen palm woody plant[36] with useful medicinal value, such as reducing fever and alleviating congestion. A component of the extract, Sotetsuflavone, was identified to have strong anti-tumor activity against lung cancer cells[37,38]. Because it can effectively induce lung cancer cell apoptosis, we studied whether it could inhibit growth, migration and invasion of malignant gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%